Perceptions of Inclusive Leadership and Its Implications for Achieving Socio-Educational Performance - Albulescu, Ion; Albulescu, Mirela; Andronache, Daniel; Manea, Adriana-Denisa; Stan, Cristian (Social Welfare: Interdisciplinary Approach, 2025)
Inclusive leadership has become a key paradigm in contemporary educational management, promoting equity, collaboration, and responsiveness to diversity. This study investigates how inclusive leadership is perceived and applied by educational leaders in the Romanian K-12 education system, while focusing on both operational leaders (teachers) and strategic leaders (principals and school inspectors). Based on a cross-sectional, non-probabilistic sample of 296 respondents, the research employed a quantitative methodology, including descriptive statistics, independent samples t-tests, multiple linear regression, and k-means cluster analysis. These methods were used to examine differences in perceptions, the influence of managerial experience and training, and the level of acceptance of inclusive leadership practices. The findings reveal significant perceptual gaps between teachers and strategic leaders, especially regarding the importance of concrete actions associated with inclusive leadership. While formal training and managerial seniority had no significant effect on acceptance levels, a critical relationship has been identified between awareness of implementation challenges and a reduced enthusiasm for the model. The study proposes a typology of three leadership profiles, specifically, practical, strategic, and adaptive, and emphasizes the need for differentiated professional development strategies tailored to each profile. These results contribute to a better understanding of how inclusive leadership can be more effectively embedded in diverse educational contexts through systemic support, reflective practice, and policy alignment.